Penerapan Sanitasi Dan Hygiene Pada Home Industry K. Pastries (Custom Birthday Cake) Di Surabaya - Astrid Larasati Luana Dwita (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
The problem in home industries related to hygiene and sanitation is the suboptimal implementation of personal hygiene practices, such as the use of APD and personal hygiene. Based on the description above, home industries, as food production facilities, are highly susceptible to microbial contamination, which can impact health if not properly managed, including hygiene and sanitation.Based on the results of this study, entitled "The Implementation of Hygiene and Sanitation in the Home Industry K. Pastries in Surabaya," the procurement of materials is in accordance with applicable procedures. Furthermore, equipment preparation is good and correct, but inadequate storage is hampered due to space limitations.